Discriminatory usefulness of pulsed-field gel electrophoresis and sequence-based typing in Legionella outbreaks. (June 2016) - Quero, Sara; García-Núñez, Marian; Párraga-Niño, Noemí; Barrabeig, Irene; Pedro-Botet, Maria L; de Simon, Mercè; Sopena, Nieves; Sabrià, Miquel
Aim: To compare the discriminatory power of pulsed-field gel electrophoresis (PFGE) and sequence-based typing (SBT) in Legionella outbreaks for determining the infection source.Materials & methods: Twenty-five investigations of Legionnaires' disease were analyzed by PFGE, SBT and Dresden monoclonal antibody.Results: The results suggested that monoclonal antibody could reduce the number of Legionella isolates to be characterized by molecular methods. The epidemiological concordance PFGE–SBT was 100%, while the molecular concordance was 64%. Adjusted Wallace index (AW) showed that PFGE has better discriminatory power than SBT (AWSBT→PFGE = 0.767; AWPFGE→SBT = 1). The discrepancies appeared mostly in sequence type (ST) 1, a worldwide distributed ST for which PFGE discriminated different profiles.Conclusion: SBT discriminatory power was not sufficient verifying the infection source, especially in worldwide distributed STs, which were classified into different PFGE patterns.